Revitalisasi Nilai-Nilai Islam pada Manajemen Madrasah: Sebuah Upaya Aktual dalam Menghadapi Ancaman Resesi 2023 - Sutrisno Sutrisno (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The threat of a recession in 2023 will not only hurt the economic aspect but also harm the educational dimension. Madrasas, as an educational institution, should be prepared to face the challenges and threats of the upcoming recession, even though this threat has not yet surfaced. One of the preventive measures that can be taken is to re-implement the urgency of Islamic values in madrasah management as an actualization in preventing the adverse effects of the 2023 recession. Considered when facing a period of disruption such as a recession. The articles in this study used the systematic literature review method with the principle of the general literature review procedure. The techniques used are coding, initial coding, and open coding by means of identification, selection, classification, evaluation, and synthesis of primary and secondary literature. As for the results of the systematic literature review that has been carried out, it shows that madrasahs, in the face of a recession, need to do the following: The first is to instill ascetic values in the madrasah system. Second, implementing sharia-based financial management. Third, reconstructing ukhuwah Islamiyah solidarity. Fourth, rejecting the usury system and transactions that are unlawful. Fourth, rebuild the transparency and accountability of madrasahs in the face of a recession. Fifth, re-implement the system of efficiency and savings in madrasas so that the danger of recession can be prevented.